Effect of health literacy on medication adherence and prognosis among patients with cardiovascular disease: a latent profile analysis - Yi Liu; Jiao Chen; Lei Xiao; Yuan Yang; Fan Zhang (Health Education Research, 2026)
Abstract To examine the association between health literacy and both prognosis and medication adherence among patients with cardiovascular disease. This single-center prospective cohort study was conducted in a tertiary hospital in Chongqing from 2022 to 2023. Health literacy was assessed using the Brief Health Literacy Screen (BHLS). Six-month follow-up evaluated Major Adverse Cardiovascular Events (MACE) and medication adherence measured by the Morisky Medication Adherence Scale (MMAS-8). Latent profile analysis (LPA) was performed using the three BHLS items, with model selection based on AIC, BIC, entropy, and the bootstrap likelihood ratio test. Logistic regression assessed associations with prognosis and adherence. Among 1 150 patients enrolled, 951 completed follow-up. 42.3% had inadequate health literacy and 172 experienced MACE. In fully adjusted models, inadequate health literacy was associated with higher odds of MACE (OR = 1.721, 95% CI 1.143–2.593) and medication non-adherence (OR = 7.864, 95% CI 4.298–14.388). Higher BHLS Item 1 scores were associated with lower odds of MACE (OR = 0.660, 95% CI 0.517–0.842). LPA identified six profiles. The lowest profile had higher odds of MACE (OR = 2.732, 95% CI 1.544–4.833). Inadequate health literacy predicted worse prognosis and medication non-adherence. Interventions should strengthen patients’ confidence in completing medical forms and understanding written information.